2007
DOI: 10.1002/chin.200742039
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular C—H Amination Reactions: Exploitation of the Rh2(II)‐Catalyzed Decomposition of Azidoacrylates.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…86 Condensation with piperonal provided the corresponding vinyl azide 9 as reported. 87 Following the reaction with triphenyl- products (L59, L62, 14) were obtained by alkylation of the corresponding (Z)-thiohydantoi ̈n with the appropriate halogenated reagent. N-Substituted analogues were prepared by displacement of the SEt group under microwave irradiation conditions with a large variety of primary and secondary aromatic amines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…86 Condensation with piperonal provided the corresponding vinyl azide 9 as reported. 87 Following the reaction with triphenyl- products (L59, L62, 14) were obtained by alkylation of the corresponding (Z)-thiohydantoi ̈n with the appropriate halogenated reagent. N-Substituted analogues were prepared by displacement of the SEt group under microwave irradiation conditions with a large variety of primary and secondary aromatic amines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Depending on the application, the ester group at the 2-position can be later modified. 9 As reported by Driver and co-workers, 10 the thermolysis of the azide and C−H amination can be performed under milder conditions in the presence of rhodium catalyst.…”
Section: ■ Synthesismentioning
confidence: 96%
“…[54][55][56] In addition, Driver reported that rhodium(II) carboxylates such as the electron-poor Rh2(O2CC3F7)4 or the electron-rich Rh2(O2CC7H15)4 can catalyze the intramolecular formation of C-N bonds from vinyl or aryl azides to provide indole and pyrrole derivatives. 57 Based on our own experience, the Du Bois catalyst bis[rhodium (α,α,α',α'-tetramethyl-1,3benzenedipropionic acid)] Rh2(esp)2, has proven to be exceptionally effective for nitrene insertion of aromatic C-H bonds. [58][59] Thus, we decided to investigate this Rh2(esp)2 catalyst nitrene aromatic insertion of 2-trichloromethyl-4-azido-pyrimidines 2.…”
Section: Scheme 5 Synthesis Of 2-trichloromethylpyrimido[45-b]indole ...mentioning
confidence: 99%